Phytic acid and grape seed extract in dentin biomodification: effects on bond strength and interface integrity - Astrid Ana Gomes; Darshana Devadiga; Roma M; Darshan Madihalli Chandramouli; Rahul D. Rao; Manikandan Ravinanthanan; Dheeraj Devadiga (Frontiers in Dental Medicine, 2026)
Background Hybrid layer degradation, driven by residual matrix metalloproteinase (MMP) activity and hydrolytic attack at the resin–dentin interface, remains a primary cause of adhesive restoration failure. Dentin biomodification using natural cross-linking agents represents a promising strategy to enhance collagen stability and inhibit enzymatic degradation of the bonded interface. Objective To evaluate and compare the effect of collagen cross linking agents, phytic acid (IP6) and grape seed extract (GSE), to reinforce the shear bond strength (SBS) of resin composite to dentin. Materials and methods Enamel of 34 human maxillary premolars was eliminated and each tooth was sectioned to make a total sample size of 68 which was divided into four groups ( n = 17) for surface treatment: G1-PA:37% Phosphoric acid (control), G2-IP6:1% phytic acid, G3-PA + GSE:37% phosphoric acid+6.5% GSE and G4-IP6 + GSE:1% phytic acid+6.5% GSE. A hybrid resin composite material was bonded and subjected to 1,000 cycles of thermocycling followed by SBS testing and analysis of fracture mode by Scanning Electron Microscopy. The data was statistically analysed using one-way Analysis of Variance (ANOVA) followed by Tukey's Honestly Significant Difference (HSD) post hoc test. Results G4-IP6 + GSE showed the highest SBS (23.44 ± 4.28 MPa), followed by G2-IP6 (21.51 ± 6.00 MPa) and G3-PA + GSE (21.01 ± 4.35 MPa), while G1-PA had the lowest values of 15.40 ± 4.60 MPa. FTIR analysis showed that phytic acid exhibited a broad peak at 3311.77 cm⁻ 1 while GSE showed peaks 3266.37 cm⁻ 1 and 1602.93 cm⁻ 1 corresponding to hydroxyl and carbonyl functional groups. Conclusion Phytic acid and grape seed extract significantly improved the composite–dentin shear bond strength of dentin. Their application appears to enhance the structural integrity of demineralized collagen at the resin–dentin interface, thereby supporting their potential incorporation into adhesive restorative protocols as a promising strategy to enhance dentin bond strength.